Effects of ibuprofen and celecoxib as neuroprotective agents in chronic cerebral hypoperfusion-induced neurodegeneration in rats - Mohd Fadly bin Mohd Noor (Kulliyyah of Medicine, International Islamic University Malaysia, 2012)
Neurodegeneration is a term that describes the progressive loss of structure or function of neurons. Common neurodegenerative diseases are Alzheimer's disease, Parkinson's disease and Huntington's disease. Neurodegeneration is always related to aging process, cerebral hypoperfusion and inflammation. In this study, an animal model for chronic cerebral hypoperfusion-related neurodegenerative diseases was created by permanent, bilateral common carotid artery occlusion (2VO) in the rat. Ibuprofen, a non-selective cyclooxygenase (COX) inhibitor and Celecoxib, a selective COX-2 inhibitor, were tested as neuroprotective agents in this experiment. The rats were divided into 4 groups; SHAM group (negative control) undergone sham operation; 2VO-O group (positive control) undergone 2VO only; 2VO-I and 2VO-C groups were treated daily with Ibuprofen and Celecoxib respectively following 2VO. After 8 weeks, all the rats were euthanized and the hippocampi were isolated. Parameters tested were the neuronal cell count in the hippocampal CA1 region, hippocampal COX-2 mRNA expression and prostaglandin E2 (PGE2) level. For initial comparison, 2VO-O group was found to have significant difference compared to SHAM, in term of increase in neuronal cell death, increase in COX-2 mRNA expression and PGE-2 level. For Ibuprofen and Celecoxib treated groups, the viable neuronal cell counts of the hippocampal CA-1 region were significantly higher compared to the 2VO-O group. For the hippocampal COX-2 mRNA expression, the value in the 2VO-I group showed no significant difference when compared to the 2VO-O group. However, the value for 2VO-C group was significantly lower compared to the 2VO-O group. For the hippocampal PGE-2 level measurement, the value in 2VO-I and 2VO-C groups were found to be significantly lower in number compared to the 2VO-O group. In conclusion, chronic cerebral hypoperfusion-induced neurodegeneration by 2VO increases the neuronal cell death in the hippocampal CA-1 region and elevates both COX-2 mRNA expression and PGE-2 level in the hippocampus. In addition, Ibuprofen and Celecoxib are shown to have neuroprotective effect in chronic cerebral hypoperfusion-induced neurodegeneration.